THE USE OF MIND MAPPING IN IMPROVING STUDENT WRITING ABILITY - Riris Mutiara Simamora, - (2010)
ABSTRACT This research entitled "The Use of Mind Mapping Technique in Improving Students' Writing Ability". It aims to find out whether mind mapping improves students' ability in increasing descriptive writing skill. To analyze the data, a quasi-experimental design was employed. It involves two eighth graders classes in a school in Bandung. Data were obtained through pre-test, post-test, and questionnaires. Data analyzed by using t-test on mind mapping technique. The questionnaires are used to investigate students' responses toward mind mapping technique. The findings show that significance value is lower than 0.05, (0.008< 0.05, r = 0.369), meaning that mind mapping improves the students' ability in writing descriptive text. In addition, data taken from questionnaire reveal that students mostly respond mind mapping positively. The students claim that this technique offers interesting learning, challenge creativity, and serves new simple technique to write especially in descriptive text. So, it is recommended for further researcher to conduct a research for other skills and other techniques.